Hadiths About Environmental Conservation - Adit Abdul Hanan; Uus Husni Hoer; Dede Sudirman; Siti Mursalina (Penerbit Hellow Pustaka, 2025)
This study is motivated by the clear obligation of man as a caliph on earth who is in charge of guarding and preserving the environment. The occurrence of environmental damage caused by human actions proves that humans have not been able to fully realize the mandate and responsibility ordered in the Quran and Hadith. Rasulullah SAW has warned humans to protect and preserve the environment. The purpose of this paper is to inventory how many traditions concerning the environment. The research method used is the literature study method. In this approach, researchers collect, analyze, and discuss information from various existing sources to formulate conclusions or new views.